Online Learning in Pandemic: The Level of Stress and Satisfaction of Pre-service Teachers - Coronel, Marilyn; Joe, Nurfaiza; Quililan, Crizy Jane; Amabao, Kayesha; Garces, Lea mae (Journal of Learning on History and Social Sciences, 2023)
The outbreak of a deadly virus called Corona has prompted schools and colleges to switch instruction from face-to-face to online learning (Masha'al et al., 2020). Even with no records nor archives of online teaching-learning, imperative steps were implemented to counterbalance the educational institutions brought by the global outbreak (Joe et al., 2022).The researcher utilized a descriptive-quantitative design. A quantitative research design is used in this study to determine the level of stress and satisfaction of pre-service teachers in online learning. It was revealed that pre-service teachers are unsure if they are stressed in online learning before the covid 19 as they have no experienced online learning before the covid 19 outbreak but very stressful during the covid 19 pandemic. On the other hand, it was also revealed that the preservice teachers were neither satisfied nor dissatisfied with the online learning set-up that they had experienced during the Covid 19 pandemic.